2011
DOI: 10.1590/s1807-59322011000200011
|View full text |Cite
|
Sign up to set email alerts
|

Early nephrology care provided by the nephrologist alone is not sufficient to mitigate the social and psychological aspects of chronic kidney disease

Abstract: OBJECTIVE:Patients with chronic kidney disease who receive early nephrology care have a better prognosis with maintenance dialysis. We aimed to determine whether early referral to a nephrologist can also improve the psychological burden of having chronic kidney disease.SUBJECTS AND METHODS:Thirty‐nine patients with chronic kidney disease that required hemodialysis were studied: 19 had a ≥ 6-month history of nephrology care (Group1), and 20 had never received any prior nephrology care (Group2). All patients par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0
2

Year Published

2012
2012
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 25 publications
(25 reference statements)
1
1
0
2
Order By: Relevance
“…We did not find any effect of the duration of nephrological care on HRQoL. This is consistent with the observations of other authors who demonstrated that although early nephrological care improves the clinical condition of CKD patients, it is not sufficient to minimize the psychosocial aspects resulting from kidney disease [ 6 ].…”
Section: Discussionsupporting
confidence: 92%
“…We did not find any effect of the duration of nephrological care on HRQoL. This is consistent with the observations of other authors who demonstrated that although early nephrological care improves the clinical condition of CKD patients, it is not sufficient to minimize the psychosocial aspects resulting from kidney disease [ 6 ].…”
Section: Discussionsupporting
confidence: 92%
“…Esto puede ser debido a que de los 3 hospitales de referencia de nuestra provincia, con atención nefrológica especializada, uno de ellos no cuenta con consulta de enfermería, y en otro, la enfermera solo dispone de un día a la semana, en el que desarrolla consulta propia de educación enfermera, dedicando el resto de días a apoyar a la consulta médica. Estudios recientes indican que la atención aportada exclusivamente por nefrólogos es insuficiente para mitigar aspectos sociales y psicológicos del paciente con ERC, los pacientes atribuyen esto al poco tiempo dedicado por los nefrólogos en la consulta y al lenguaje que utilizan (36) .…”
Section: Discussionunclassified
“…In particular, late referral to nephrologists is associated with poor outcomes and increased mortality and morbidity, 4 6 whereas early referral to nephrology departments allows sufficient predialysis education, which can delay the initiation of dialysis and improve mortality rates. 7 , 8 However, predialysis nephrology care fails to decrease the social impact of CKD, 9 and a cooperative intervention with nephrologist-based multidisciplinary care (MDC) was developed to improve positive attitudes for disease management among patients with CKD. This level of care has a substantial influence on mortality and morbidity and delays entry into hemodialysis.…”
Section: Introductionmentioning
confidence: 99%